A century of fiction in the New Yorker : 1925-2025 - Treisman, Deborah, 1970- (Alfred A. Knopf, 2025)
"Edited by The New Yorker's fiction editor, Deborah Treisman, a celebratory selection from 100 years of short stories in the magazine which has been the most influential and important showcase for the form and has launched dozens of stellar careers in fiction Adichie, Borges, Carver, Cheever . . . Danticat, DeLillo, Diaz, Erdrich, Gaitskill . . . Lahiri, Moore, Munro, Murakami . . . Nabokov, O'Hara, Paley, Rushdie, Saunders, Sontag . . . Trevor, Updike, Welty, Wolff...There is simply no A-Z like the alphabet of fiction writers who have appeared in the pages of The New Yorker in the last hundred years. The book boasts inarguable classics like Salinger's "A Perfect Day for Bananafish," Annie Proulx's "Brokeback Mountain," and Shirley Jackson's "The Lottery" alongside stunners to be rediscovered. Some stories defined a moment or a now lost world (Isaac Bashevis Singer's "The Cafeteria"); others showed us a whole new way fiction could sound and feel ("The Red Girl," by Jamaica Kincaid). With this vivid selection, Treisman showcases how our fiction has changed over time, and reminds us that past literary fashions continue to ripple outward in the fiction we love today. What does a Donald Barthelme mean to the craft of short fiction now? What will a Yiyun Li mean to the next generation of readers and writers? This exquisite tour of the form as practiced at its highest level will leap directly into the hearts of readers of all ages, all stripes, and is a beautiful tribute to the magazine's influence on our literary culture over the last century"--